2012
DOI: 10.1016/j.protis.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Expressed Sequence Tags from the Marine Microalga Pseudochattonella farcimen (Dictyochophyceae)

Abstract: Pseudochattonella farcimen (Eikrem, Edvardsen, et Throndsen) is a unicellular alga belonging to the Dictyochophyceae (Heterokonta). It forms recurring blooms in Scandinavian coastal waters, and has been associated to fish mortality. Here we report the sequencing and analysis of 10,368 expressed sequence tags (ESTs) corresponding to 8,149 unique gene models from this species. Compared to EST libraries from other heterokonts, P. farcimen contains a high number of genes with functions related to cell communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 88 publications
1
8
0
Order By: Relevance
“…stramenopile oomycetes. However, a study has recently confirmed the presence of at least two different putative PKS III in Pseudochattonella farcimen from another class of ochrophytes, the Dichtyochophyta (Dittami et al, 2012b). These data corroborate the fact that a lateral transfer of PKS III gene has occurred after separation of diatoms from other ochrophytes, but before the divergence of brown algae with pelagophytes and dichtyochophytes.…”
Section: Discussionmentioning
confidence: 67%
“…stramenopile oomycetes. However, a study has recently confirmed the presence of at least two different putative PKS III in Pseudochattonella farcimen from another class of ochrophytes, the Dichtyochophyta (Dittami et al, 2012b). These data corroborate the fact that a lateral transfer of PKS III gene has occurred after separation of diatoms from other ochrophytes, but before the divergence of brown algae with pelagophytes and dichtyochophytes.…”
Section: Discussionmentioning
confidence: 67%
“…Expressed sequence tags (EST) library has been analyzed in strains from P. farcimen (Dittami et al. ).…”
mentioning
confidence: 99%
“…Nuclear-, chloroplast-, and mitochondrial-encoded DNA sequences identified one strain isolated from German North Sea in 2000 as P. verruculosa, whereas strains from Skagerrak isolated in 2001 and 2006 belonged to P. farcimen (Riisberg and Edvardsen 2008). Expressed sequence tags (EST) library has been analyzed in strains from P. farcimen (Dittami et al 2012).…”
mentioning
confidence: 99%
“…; Dittami et al . ). All three examples demonstrate the importance of bacteria as actors that have shaped the evolutionary history of the algae they co‐existed with.…”
Section: Algae As ‘Superorganisms’ In a Changing Environmentmentioning
confidence: 97%